GROWTH AND NUTRICIONAL ASPECTS OF THE AUSTRALIAN KING PALM TREE, UNDER DIFFERENT SPACING BETWEEN PLANTS, IN THE PARANÁ COAST, BRAZIL - RUIZ FILHO, Ricardo Razuk; MARQUES, Renato; ROCHA, Aline Alinéia (Scientia Agraria, 2009)
The growth dynamics and some nutritional aspects of the king palm tree (Archontophoenix cunninghamiana) were evaluated in a plantation placed on Inceptisol, in the county of Paranagua, in the Paraná State, using the following spacing between plants as treatments (T1 - 0,80 x 0,80 m; T2 - 1,00 x 0,80 m; T3 - 1,50 x 0,50 m e T4 - 1,20 x 0,60 m). Planting was realized in 2001; the stem height and diameter of plants were evaluated after 12, 20 and 28 months of planting. N, P, K, Ca and Mg contents in leaves were evaluated 12, 16, 20, 24 and 28 months after planting. The height of plants was affected by spacing between plants but not the stem diameter. The same effect was observed for foliar Mg content, probably related to the higher incorporation of Mg by the taller plants more exposed to sun radiation. The N content in the leaves was different when comparing the leaf blade and the leaf raquis suggesting the leaf blade to be more appropriate for foliar analysis.